Application of Shear-Wave Elastography in the Evaluation of Hamstring Stiffness in Young Basketball Athletes - Paige Cummings; Nathan D. Schilaty; Takashi Nagai; Luca Rigamonti; Ryo Ueno; Nathaniel A. Bates (North American Sports Medicine Institute, 2022)
# Background Previous literature has postulated a relationship between greater hamstring stiffness and a higher risk of sustaining injury. Shear wave elastography (SWE) presents a relatively new means for non-invasive evaluation of soft tissue elasticity pre- and post- injury or intervention. # Purpose (1) To establish baseline hamstring stiffness measures for young competitive athletes and (2) determine effect of targeted neuromuscular training (TNMT) on shear wave stiffness of the hamstring. # Study Design Un-blinded, prospective, non-randomized, cohort study. # Methods Six-hundred forty-two lower extremities from 321 high school and collegiate basketball athletes (177 F: 139 M) were examined for hamstring stiffness prior to the start of their competitive basketball season. Teams were cluster assigned to either the control or intervention (TNMT) group. Subjects in the control group underwent regular season activities as directed, with no influence from the research team. For the TNMT group, the research team introduced a hamstring targeted dynamic warm-up program as an intervention focused on activating the hamstring musculature. # Results Collegiate status was significant to hamstring stiffness for both sexes (p ≤ 0.02), but hamstring stiffness did not correlate to age or sex (r^2^ ≤ 0.08). Intervention was a significant factor to hamstring stiffness when the hip was positioned in extension (p ≤ 0.01), but not in deeper flexion (p = 0.12). This effect was sex-specific as TNMT influenced hamstring stiffness in females (p = 0.03), but not in males (p ≥ 0.13). Control athletes suffered three HAM injuries; TNMT athletes suffered 0 hamstring injuries. # Conclusion Higher SWE measurements correlated with increased risk of injury, male sex, and collegiate athletics. TNMT intervention can lessen muscle stiffness which may reduce relate to injury incidence. Intervention effectiveness may be sex specific. # Level of Evidence II